The second hemiphlebiid damselfly (Odonata: Zygoptera) from mid-Cretaceous Burmese amber. Issue 2 (3rd April 2019) - Zheng, Daran; Wang, Bo
Abstract : Zheng, D. & Wang, B., November, 2018. The second hemiphlebiid damselfly (Odonata: Zygoptera) from mid-Cretaceous Burmese amber. Alcheringa 43, 257–260. ISSN 0311-5518. Burmahemiphlebia zhangi Zheng et al., 2017 is the dominant damselfly found in Burmese amber. Here, a new hemiphlebiid damselfly, Burmahemiphlebia hui sp. nov., is described representing the second Burmahemiphlebia species discovered in Burmese amber. Burmahemiphlebia hui sp. nov. differs from Burmahemiphlebia zhangi in having more postnodal cross-veins, CuP and the separating point of AA from AP basal of A × 1, Arc aligned with A × 2, RP2 base closer to N than to Pt, and IR1 five cells distal of RP2 base. The new damselfly is extremely rare and the only one known from Burmese amber, unlike Burmahemiphlebia zhangi . Daran Zheng* [dranzheng@gmail.com ], Bo Wang† [bowang@nigpas.ac.cn ] State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology and Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, PR China. *Also affiliated with: Department of Earth Sciences, The University of Hong Kong, Hong Kong Special Administrative Region, PR China. †Also affiliated with: Shandong Provincial Key Laboratory of Depositional Mineralization & Sedimentary Minerals, Shandong University of Science and Technology, Qingdao, Shandong 266590, PR China and Key Laboratory of Zoological Systematics and Evolution, Institute of Zoology, Chinese Academy of Sciences, Beijing 100101, PR China.